2016
DOI: 10.1002/hed.24176
|View full text |Cite
|
Sign up to set email alerts
|

Association of the upregulated expression of focal adhesion kinase with poor prognosis and tumor dissemination in hypopharyngeal cancer

Abstract: The current study demonstrated that upregulated FAK expression correlates with poor prognosis and tumor dissemination in surgically treated patients with hypopharyngeal cancer. © 2016 Wiley Periodicals, Inc. Head Neck 38:1164-1169, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…As in our study, FAK overexpression has previously been reported in many cancers [42], including NSCLC and SCLC [19,33,34,43,44,45,46]. Moreover, FAK overexpression has been associated with poor survival in various cancers [12,14,20,22,47,48]. In NSCLC, however, discordant results have been reported.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As in our study, FAK overexpression has previously been reported in many cancers [42], including NSCLC and SCLC [19,33,34,43,44,45,46]. Moreover, FAK overexpression has been associated with poor survival in various cancers [12,14,20,22,47,48]. In NSCLC, however, discordant results have been reported.…”
Section: Discussionsupporting
confidence: 78%
“…Once activated by integrins, G protein-coupled receptor ligands, or growth factors and neuromediators, FAK is autophosphorylated at tyrosine 397 (Y397), then binds and activates downstream proteins such as Src, p130CAS, paxillin, and PI3KR2 [7,8,9], finally leading to cell adhesion, migration, invasion, survival, proliferation, angiogenesis, immune suppression, and regulation of DNA damage repair [8,9,10,11]. Because of these roles and its overexpression in many cancers, with the correlation to poor prognosis in some of them [12,13,14,15,16,17,18,19,20,21,22,23], FAK is believed to play a role in cancer development and progression. Small-molecule inhibitors targeting the FAK kinase domain (e.g., PF-573,228) have, therefore, been developed as potential anti-cancer targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The full text of the remaining 42 citations was then carefully read, and twelve articles were subsequently excluded. Of the excluded articles, five employed an alternative survival endpoint instead of OS [ 23 27 ], five had no data available[ 8 , 13 14 , 28 30 ], one divided the FAK level into three or more groups [ 30 ], and one article treated FAK scores as a continuous variable[ 31 ]. A total of 30 studies were thus ultimately included in our meta-analysis ( Fig 1 ) [ 10 , 15 , 16 , 32 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, upregulated FAK expression was correlated with poor prognosis and tumor dissemination in hypopharyngeal cancer patients [20]. Similarly, high FAK expression in triple-negative breast cancer was associated with lymphovascular invasion and shorter overall and progression free survival [21].…”
Section: Discussionmentioning
confidence: 99%